Surau-Based Community Counseling Service to Increase Psychological Resilience of Ms. Majelis Ta'lim in Nagari Terindah Pariangan, West Sumatra - Silvianetri, Silvianetri; Irman, Irman; Rozi, Azzuhri (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2022)
: Low psychological resilience makes mothers take actions that are not in accordance with religious, customaryand community norms. The purpose of this service is to increase the psychological resilience of the majlis ta'lim womenof Nagari Pariangan through community counseling services based on surau. The service is carried out to thecommunity of mothers of taklim majlis who routinely conduct recitations with a total of 49 people, with an age range of27 to 65 years. The ta'lim assembly was led by Mrs. JS, who is 58 years old who works as a teacher. The service methoduses the participatory action research (PAR) method with eleven steps of activity. In this service, it is empiricallyproven that surau-based counseling services can increase the psychological resilience of majlis ta'lim mothers in NagariPariangan, Tanah Datar, West Sumatra. This service is expected to be a stimulus for other devotees who are interestedin making social changes in the community.